Totalitaryzm a PRL - Kofman, Jan (Civitas. Studia z filozofii polityki, 2012)
Was the PRP an incomplete authoritarianism, a version of corporativism, a new generation of dictatorship, a mixture or a resultant of these classifications in different ratios, or, perhaps, a totalitarian system after all? Our choice of response defines the content of the memory of the common past to which we refer, it determines our attitude to the question of its appraisal and settlement and, consequently, it also raises the issue of the personal squaring of accounts with it. Totalitarianism in its extreme form did not occur in the PRP, apart from the early nineteen fifties, when the situation in the country was close to it. Periods of liberalisation were interspersed with regressive turnabouts. Until 1988/89, the system which existed in Poland was decisively dominated by the totalitarian elements contained within it, which the communist party resorted to in order to maintain its power.